Yeast and its Importance to Wine Aroma - A Review - Lambrechts, M.G.; Pretorius, I.S. (South African Journal of Enology and Viticulture, 2019)
The most mysterious aspect of wine is the endless variety of flavours that stem from a complex, completely non-linear system of interactions among many hundreds of compounds. In its widest sense, wine flavour refers to the overall impression of both aroma and taste components. Aroma is usually associated with odorous, volatile compounds; the bouquet of wine refers to the more complex flavour compounds which evolve as a result of fermentation, elevage and ageing. With the exception of terpenes in the aromatic grape varieties and alkoxypyrazines in the herbaceous cultivars, perceived flavour is the result of absolute amounts and specific ratios of many of these interactive compounds, rather than being attributable to a single "impact" compound. Without underestimating the complexity of these interactive effects or negating the definitive role played by the accumulated secondary grape metabolites in the varietal character of wine, this review will focus mainly on the contribution of yeast fermentation to the sensorial quality of the final product. Yeast and fermentation conditions are claimed to be the most important factors influencing the flavours in wine. Both spontaneous and inoculated wine fermentations are affected by the diversity of yeasts associated with the vineyard and winery. During the primary alcoholic fermentation of sugar, the wine yeast, Saccharomyces cerevisiae, together with other indigenous non-Saccharomyces species, produce ethanol, carbon dioxide and a number of by-products. Of these yeast-derived metabolites, the alcohols, acetates and C4-C8 1tfatty acid ethyl esters are found in the highest concentration in wine. While the volatile metabolites contribute to the fermentation bouquet ubiquitous to all young wines, the production levels of these by-products are variable and yeast strain specific. Therefore, this article also highlights the importance of untapping the hidden wealth of indigenous yeast species present on grapes, and the selection and genetic development of yeast starter culture strains with improved flavour profiles. In the future, some winemakers may prefer to use mixtures of indigenous yeast species and tailored S. cerevisiae strains as starter cultures to reflect the biodiversity and stylistic distinctiveness of a given region. This will help winemakers to fullfil the consumer’s demand for individual wines with intact local character and to ensure the survival of wine’s most enthralling aspect - its endless variety.